Cultural codes : makings of a Black music philosophy : an interpretive history from spirituals to hip hop - Banfield, William C., 1961- (African American cultural theory and heritage., 2010)
"No art can survive without an understanding of, and dedication to, the values envisioned by its creators. No culture over time has existed without a belief system to sustain its survival. Black music is no different. In Cultural Codes: Makings of a Black Music Philosophy, William C. Banfield engages the reader in a conversation about the aesthetics and meanings that inform this critical component of our social consciousness." "By providing a focused examination of the historical development of Black music artistry, Banfield formulates a useable philosophy tied to how such music is made, shaped, and functions. In so doing, he explores Black music culture from three angles: history, education, and the creative work of the musicians who have moved the art forward. In addition to tracing Black music from its African roots to its various contemporary expressions, including jazz, soul, R&B, funk, and hip hop, Banfield profiles some of the most important musicians over the last century: W.C. Handy, Scott Joplin, Louis Armstrong, Duke Ellington, Count Basie, Mary Lou Williams, John Coltrane, James Brown, Jimi Hendrix, and Stevie Wonder, among others. Cultural Codes provides an educational and philosophical framework for students and scholars interested in the traditions, the development, the innovators, and the relevance of Black music."--BOOK JACKET.